Health care utilization among individuals who die by suicide as compared to the general population: a population-based register study in Sweden - Elisabeth Bondesson; Tori Alpar; Ingemar F. Petersson; Maria E. C. Schelin; Anna Jöud (BMC, 2022)
Abstract Background Globally, 700 000 people die every year by suicide. Health care consultation patterns the period before suicide could be one potential way to identify people at risk for suicide. Therefore, this study examines health care patterns up to one year prior to the suicide by age, sex and prior diagnoses and specifically investigates if and how this differs from the general population of Skåne, Sweden. Methods This cohort study includes all individuals, aged 15 and older, that died by suicide in Region Skåne, Sweden from 2004 to 2015 (n = 1653). The individuals were identified through the Cause of death register and then linked to the Skåne healthcare register. Health care data was analyzed as proportions consulting different types of health care the month and year preceding the suicide, we also investigated the impact of age, sex and the occurrence of prior psychiatric and pain diagnoses. Additionally, we compared the proportion of consulting care among the suicide victims and the general population of Skåne. Results In the month before their death, 53% of the suicide victims had any health care consultation, compared with 20% in the general population of Skåne, a given month (p < 0.0001). The corresponding figures for the year prior to suicide was 86% among those who died by suicide, compared to 69% in the general population of Skåne, a given year (p < 0.0001). Women, and those having a documented history of psychiatric diagnosis were more likely to have health care consultations in the month and year preceding suicide (p < 0.001), compared to men and suicide victims without a history of psychiatric disease. Older adults that died by suicide, were less likely to consult psychiatric care compared to the younger suicide victims (p < 0.001). Conclusion A majority of the suicide victims consulted health care in the near time before death and the proportion of seeking health care was significantly higher than in the general population of Skåne and higher among female suicide victims as compared to males. Alternative preventive screening measures should be considered for individuals consulting health care, especially for older people and individuals outside the psychiatric care.